Performance Optimization of Photovoltaic Thermal System under UAE Climate Condition: Experimental and Simulation Analysis - ALSHAAER, SHEIKHA ALI (2021)
One of the worldwide challenges is reducing energy consumption to reduce greenhouse gas (GHG) emissions that are associated with energy production and use. Delay in taking proper action will lead to the catastrophic effect of global warming (Ghoneim, 2016). In general, until today, the majority of energy is produced from fossil fuel sources (Riffat, 2011). There are various reasons for still depending on fossil fuel resources to produce energy. Fossil fuel energy has a lower production cost than renewable energy (Sharma, 2016). In addition, fossil fuel is very efficient in producing energy. On the other hand, generating power from solar energy is considered to be a promising solution. However, the Photovoltaic system has low efficiency resulting from the low conversion factor of Photovoltaic cells (Shaneb & other 2017). Accordingly, various researchers focused on enhancing the PV performance through avoiding shading and, using the sun tracking system. Photovoltaic thermal is considered to be one of the methods used to enhance the electrical performance of PV systems. The main working principle of PVT is passing fluid at the back of the PV panel that removes the excess heat from the PV panel surface and enhances electrical efficiency. The fluid used in PVT is either water, air, or refrigerant (Shaneb et al, 2017). The aim of performing the test was to evaluate and assess both electrical and thermal performance of the PVT system, under UAE climate conditions, in the first phase of the study. Then, enhance the performance of PVT, by optimizing some of the design parameters. To achieve the project aims, the research started with a review of previous studies related to PVT. The literature review focused on data required to be collected during the experimental phase, the capability of TRNSYS software, and optimization parameters. Therefore, the research methodology has been carried out in two parts: experimental and simulation. In the first part, the performance of PVT, in comparison with PV panel, was tested experimentally. The collected data from the experiment were utilized to develop a simulation model to represent PVT by using TRNSYS software. The simulation model was used to optimize the PVT performance by changing some of the design parameters. The design parameters were: number of collector tubes, tubes diameter, and PVT panel area, and water flow rates. Experimental results showed that the enhancement in electrical efficiency of PVT in winter was 0.7%, which is equal to 5% more in comparison with PV. The results in summer were 1.2%, which is equal to 8.9% more in comparison with PV panel. The overall PVT efficiency in winter was 53.8%, and in summer the overall PVT efficiency was 57.1%. A simulation model was developed for the PVT system, based on data collected from the experiment. The model has been validated, comparing the experimental results with simulation results, with a tolerance of 5% error. In the simulation part, some design parameters were optimized by testing a range of values: number of collector tubes, tubes diameter, PVT panel area, and water flow rates. The aim of changing the design parameters was to optimize the performance of PVT during winter and summer. The results showed that the optimum number of collector tubes was 12 tubes; the optimum tube diameter was 0.04 m; and the water flow rate was 2.5 GPM in both winter and summer. In addition, results showed that changing the PVT area was not feasible. There was no enhancement in the overall efficiency. Based on the identified optimum values of design parameters, the optimized model was created. The results from the optimized model showed further enhancement in comparison with the reference model. The percentage of electrical efficiency enhancement of PVT was 7.2% in winter and 7.5% in summer, compared to the reference model. In addition, the research compared the electrical performance of the PV panel with the PVT optimized model. The electrical efficiency of the PVT optimized model provided higher electrical efficiency than the PV panel by 6% during winter and 10% during summer.